Hematoma-induced Twiddler-like phenomenon as a presentation of DBS hardware failure: Case report - Holland, Marshall T.; Alvarado-Gonzalez, Abraham; Wong, Joshua K.; Almeida, Leonardo Brito de; Wagle Shukla, Aparna; Deeb, Wissam; Patterson, Addie; Okun, Michael S.; Foote, Kelly D. (Frontiers in Human Neuroscience, 2023)
Deep brain stimulators (DBS) may fail for a multitude of reasons. We present a 79-year-old Parkinson’s disease patient who suffered a DBS failure following impulse generator (IPG) replacement surgery due to the IPG flipping within an expanded capsular pocket. This creation of the pocket was unintentional, and the pocket formed around an undiagnosed postoperative hemorrhage. The syndrome could be considered “Twiddler-like” because it resulted in device flipping. There were, however, many characteristic differences between our case and classical Twiddler’s syndrome. DBS neurostimulator failure due to hematoma induced device flipping should be suspected when device interrogation is impossible or there are abnormally high impedances across multiple DBS lead contacts. A plain film X-ray series should be ordered and can be useful in providing radiological evidence of device flipping. In cases like ours the extensive braiding encountered in Twiddler’s syndrome may be absent. Anchoring the IPG to a deep fascial layer as well as the use of an antimicrobial pouch are two methods that may be employed to prevent or to treat this complication.